The Organizational Design of Transnational Professional Service Firms - Morris, T; Greenwood, R; Fairclough, S; Boussebaa, M (2010)
Large transnational professional service firms (PSFs) are highly influential in today's global economy because they underpin the integrity of financial markets, enable complex international transactions, and deliver ideas and advice to the world's largest corporations and governments. They sell expertise – that most intangible of outputs – and they seek to provide customized solutions to demanding clients on a global basis. Many other businesses will face similar challenges in the 21st century, as the world becomes more globally connected and customers become more demanding, seeking customized products or services that fit their particular needs. As such, professional service firms – of which accounting, law, and consulting are prime examples – are critical corporate players in the 21st century. PSFs also face significant managerial challenges. Over the past few decades, they have grown in complexity, both geographically and in size, to the point where traditional organizational arrangements have proven inadequate. How have PSFs responded, and what lessons can we draw? Our ongoing studies of PSFs show the emergence of a “multiplex” organizational form. Organizations that are successfully implementing the multiplex design are responding to their complex environments by developing highly differentiated structures in order to capture the benefits of deep specialization along several axes. The trick, however, is in pulling these differentiated parts together. The risk that high differentiation will overpower attempts at coordination was responsible for the earlier failure in various industries of the two-dimensional matrix organizational form. But transnational PSFs have gone further by using three axes of differentiation – and appear to have done so successfully. They have discovered how to gain the powerful benefits of multidimensional specialization without losing overall coordinated effort. First, transnational PSFs have developed multiple axes of deep expertise with respect to their professional services, clients, and markets. Second, professionals within these firms are members of multiple practice groups and teams that criss-cross the multiple axes of expertise, thereby creating a landscape of nascent communities in which personal networks can flourish and expert knowledge can be identified. Third, the deep specialization and experience embodied in a firm's resources are pulled together and harnessed via a client management system, an integrative mechanism which classifies and sorts clients according to various strategic and operational criteria, assigns responsibility for each to appropriate senior professionals (partners), and assists in creating semi-permanent or bespoke client teams to address the needs of a client or specific engagement. Fourth, and perhaps most important, cooperation and coordination are achieved through a culture of reciprocity that is developed and sustained by a number of strategic, organizational, and normative processes within the firm. In this article, we elaborate on this promising organizational design for the 21st century. We use accounting firms as our example, because they are exemplars of the knowledge-intensive, multiplex organizational form, but our research in other professional service organizations confirms that they, too, are using the same practices to develop the same design template. We begin by outlining the challenges for which this organizational form is the emerging solution.